Mineralized Cartilage and Bone-Like Tissues in Chondrichthyans Offer Potential Insights Into the Evolution and Development of Mineralized Tissues in the Vertebrate Endoskeleton - Atake, Oghenevwogaga J.; Eames, B. Frank (Frontiers in Genetics, 2021)
The impregnation of biominerals into the extracellular matrix of living organisms, a process termed biomineralization, gives rise to diverse mineralized (or calcified) tissues in vertebrates. Preservation of mineralized tissues in the fossil record has provided insights into the evolutionary history of vertebrates and their skeletons. However, current understanding of the vertebrate skeleton and of the processes underlying its formation is biased towards biomedical models such as the tetrapods mouse and chick. Chondrichthyans (sharks, skates, rays, and chimaeras) and osteichthyans are the only vertebrate groups with extant (living) representatives that have a mineralized skeleton, but the basal phylogenetic position of chondrichthyans could potentially offer unique insights into skeletal evolution. For example, bone is a vertebrate novelty, but the internal supporting skeleton (endoskeleton) of extant chondrichthyans is commonly described as lacking bone. The molecular and developmental basis for this assertion is yet to be tested. Subperichondral tissues in the endoskeleton of some chondrichthyans display mineralization patterns and histological and molecular features of bone, thereby challenging the notion that extant chondrichthyans lack endoskeletal bone. Additionally, the chondrichthyan endoskeleton demonstrates some unique features and others that are potentially homologous with other vertebrates, including a polygonal mineralization pattern, a trabecular mineralization pattern, and an unconstricted perichordal sheath. Because of the basal phylogenetic position of chondrichthyans among all other extant vertebrates with a mineralized skeleton, developmental and molecular studies of chondrichthyans are critical to flesh out the evolution of vertebrate skeletal tissues, but only a handful of such studies have been carried out to date. This review discusses morphological and molecular features of chondrichthyan endoskeletal tissues and cell types, ultimately emphasizing how comparative embryology and transcriptomics can reveal homology of mineralized skeletal tissues (and their cell types) between chondrichthyans and other vertebrates.